(untitled) (Current Horticulture, 2024)
The experiment was conducted using two-factor CRD with IBA concentrations (0, 250, 500, 750 and 1000 ppm) and stem cuttings of stems (5, 10 and 15 cm) lenth of dragon fruit (Hylocereus polyrhizus) plant replicated thrice at Department of Horticulture, Nagaland University,SASRD, Medziphema, during 2016-17. The shoot growth and establishment of stem cuttings in field were best achieved with the application of IBA 1000 ppm even with smaller-sized cuttings of stems, while total nitrogen and protein content (%) were more with lower concentration of IBA (250 ppm). The cutting size of 15 cm recorded good shoot and root development even without the application of IBA. There was cent per cent survival of stem cuttings after one year of their planting.